Smartphone Applications Used for Initiating and Maintaining Physical Activity: An Exploratory Analysis - Aroni, Andre; Castillo, Elmer; Sousa, Catarina [UNESP]; Machado, Afonso [UNESP]; Filho, Edson; Tenenbaum, Gershon (Univ Illes Balears, 2018)
The aim of this study was to explore the degree to which smartphone-based fitness applications help people start and maintain a regular physical activity across North America, South America and Europe. This descriptive and exploratory study consisted of 904 respondents from three continents. A survey composed of demographic questions, closed questions, and scales with Likert-type responses was developed and distributed via social media. Findings revealed that 52.3% of the participants in South America, 72.7% in North America, and 80.1% in Europe had downloaded a physical activity app on their smartphones. Of these participants, 8.1% in South America, 5.9% in North America, and 1.9% in Europe reported that the application helped them very much in beginning an exercise regimen. Similarly, 8.9% from North America, 6.9% from Europe, and 7.1% from South America reported that it helped them very much to maintain their already implemented exercise regimen. The findings revealed that fitness applications for smartphones have limited effect on exercise engagement; for the majority who download them, the apps remain unused, and at this stage did not become part of their internal state of mind.
Keywords: smartphones; applications; physical activity; motivation